Diversity Management on the Salary for Job Satisfaction CV. Megah Persada Indonesian Dynasty - Harjanti, Wulandari; Hardiyanto, Gamma; Cahyo Nugroho, Dodit (Action Research Literate, 2024)
This research aims to analyze the influence of diversity management on employee job satisfaction in CV. Megah Persada Indonesian Dynasty, with a special focus on the compensation or salary aspect. Diversity management is one of the important elements in creating an inclusive work environment, which is expected to increase employee satisfaction and productivity. In this study, a quantitative method was used by collecting data through a survey of company employees. The results show that good diversity management, especially in terms of fair and balanced payroll policies, contributes significantly to the increase in employee job satisfaction. These findings emphasize the importance of diversity management in creating a harmonious and productive work environment, as well as provide practical implications for companies in formulating policies related to human resource management.